Applying Read, Cover, Remember, Retell (RCRR) Strategy to Foster Students’ Reading Comprehension of Descriptive Text - Enggar Relawati; Didin Nuruddin Hidayat; Atiq Susilo (Universitas Cokroaminoto Palopo, 2020)
The aim of this study was to obtain the empirical evidence of the Effect of applying Read, Cover, Remember, Retell (RCRR) Strategy on Students’ Reading Comprehension of Descriptive Text at the Tenth-Grade students of SMA Muhammadiyah 8 Ciputat in Academic Year 2018/2019. The population sample of this study was 54 students selected by purposive sampling technique and was divided into two classes; X IPS 3 as the experimental class, was treated using RCRR strategy and X IPS 2 as the controlled class, was treated without using RCRR strategy. The method that was used in the study was a quantitative method using quasi-experimental design. The data was analyzed by using t-test. The results obtained from this study showed the heterogeneity of student performance in reading comprehension of descriptive text after applying RCRR strategy and without applying the strategy. The result showed a post-test score p-value of 0.001 with a meaning rate of 0.05 (5%). In other terms, the p-value (0.001) < sig α= 0.05 (5%) is provided. Therefore, the outcome of the effect size was 1.47. It proved that using the RCRR strategy was effective to use at a strong level on students’ reading understanding of descriptive text at the tenth-grade students of SMA Muhammadiyah 8 Ciputat at a strong level.